2019
DOI: 10.1044/2019_jslhr-h-18-0407
|View full text |Cite
|
Sign up to set email alerts
|

Time-Gated Word Recognition in Children: Effects of Auditory Access, Age, and Semantic Context

Abstract: Purpose We employed a time-gated word recognition task to investigate how children who are hard of hearing (CHH) and children with normal hearing (CNH) combine cognitive–linguistic abilities and acoustic–phonetic cues to recognize words in sentence-final position. Method The current study included 40 CHH and 30 CNH in 1st or 3rd grade. Participants completed vocabulary and working memory tests and a time-gated word recognition task consisting of 14 high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 72 publications
5
15
0
Order By: Relevance
“…Children with a larger lexicon performed significantly better in restoring words in sentences regardless of their working memory and attention control abilities. This specific finding is also consistent with results of Walker and colleagues [ 49 ] who studied time-gated speech recognition in children with mild to moderate hearing loss. Walker et al [ 49 ] found that vocabulary, not children’s verbal WMC, mediated the relation between audibility and time-gated word recognition.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Children with a larger lexicon performed significantly better in restoring words in sentences regardless of their working memory and attention control abilities. This specific finding is also consistent with results of Walker and colleagues [ 49 ] who studied time-gated speech recognition in children with mild to moderate hearing loss. Walker et al [ 49 ] found that vocabulary, not children’s verbal WMC, mediated the relation between audibility and time-gated word recognition.…”
Section: Discussionsupporting
confidence: 92%
“…An interesting additional finding was that there was no interaction between lexical context and modality, which suggested that when listening in noise, lexical factors did not significantly advantage speech perception in the audio-visual condition. Recently, Walker and colleagues [ 49 ] examined the role of working memory and vocabulary on time-gated word recognition in children with hearing loss. They found that lexical knowledge, not working memory capacity, mediated the relationship between audibility and recognition of time-gated words.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To this end, though improving vocabulary knowledge for children who use CIs is necessary for future literacy success (Lund, 2016), doing so may not lead to phonological awareness gains. It is possible that vocabulary could mediate the relationship between auditory access and phonological sensitivity (as it appears to do for children who are hearing aid users, see Walker et al, 2019), which would also explain the correlations between vocabulary and phonological sensitivity found in school-aged children who use CIs. We suggest that in the event that vocabulary does serve as a mediator, it does so after children have passed through the prereading stage, when they have learned more words.…”
Section: Co-development Of Oral Language and Phonological Sensitivitymentioning
confidence: 99%
“…The reality, however, is that many children continue to have reduced auditory access. For example, only half of the sample of CI users achieve full-time use (indexed as 80% of waking hours) by age 3 years, indicating that many children who use CIs are not receiving sufficient auditory access to drive emergent literacy development (Walker et al, 2019). Rather, children who use CIs are likely to require specialized intervention in both vocabulary and morphosyntax to promote academic success (Lonigan and Shanahan, 2010).…”
Section: Co-development Of Language Constructsmentioning
confidence: 99%